Testing the no-hair theorem with the continuum-fitting and the iron line methods: a short review. (24th February 2016) - Bambi, Cosimo; Jiang, Jiachen; Steiner, James F
Abstract: The continuum-fitting and the iron line methods are leading techniques capable of probing the spacetime geometry around astrophysical black hole candidates and testing the no-hair theorem. In the present paper, we review the two approaches, from the astrophysical models and their assumptions, to the constraining power with present and future facilities.